Qualidade do ar oriunda de tráfego urbano em uma cidade de porte médio - Daris, Denise Pacheco (2015)
The Passo Fundo city as well as the most cities has many atmospheric emissions generators that don t have control and monitoring means, which can generate a several types of pollutants. These pollutants can cause acute and chronic effects to the human health, besides causing local and global environmental impacts. Considering that there are a few cities in the world performing monitoring practices and air emissions inventory, it s fundamental the importance of the information to diagnose the impacts and, if necessary, provide control measures in the generating sources. This study aimed to evaluate the air pollution coming from the urban traffic in Passo Fundo, enabling civil society, governments and institutions actions. For this, the air quality was monitored and analyzed, during the period from April 2014 to March in 2015, with passive samplers, through the nitrogen dioxide (NO2) and ozone (O3) pollutants that are produced by the vehicle emissions. It was possible to observe the effect of vehicle emissions through the nitrogen dioxide and ozone concentrations which are emitted due the fossil fuel burning and can be associated or not to the ozone production through the photochemical phenomena. The values found meet the provisions of current legislation. The data also showed a connection between the pollutants and meteorological factors